2017
DOI: 10.1017/s1751731116002603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentrate feeding sequence on equine hindgut fermentation parameters

Abstract: Feeding a diet with a small amount of hay and a high proportion of concentrate given in large meals entails a risk of colic to horses as this can impact the hindgut microbial ecosystem. To counteract this potential negative effect, one feeding strategy is to modify the distribution sequence of concentrate and hay. The purpose of the present study was to assess the impact of feeding the concentrate meal before or with the hay meal on fermentative parameters postprandial variations in caecum and right ventral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…the sternal flexure, pelvic flexure, right dorsal colon and rectum) compared with those fed the HF diet. This finding corroborates those of other studies [ 21 , 26 ] which show that horses fed diets with a high starch content contain high concentrations of total VFAs across all segments of the intestinal tract.…”
Section: Discussionsupporting
confidence: 92%
“…the sternal flexure, pelvic flexure, right dorsal colon and rectum) compared with those fed the HF diet. This finding corroborates those of other studies [ 21 , 26 ] which show that horses fed diets with a high starch content contain high concentrations of total VFAs across all segments of the intestinal tract.…”
Section: Discussionsupporting
confidence: 92%
“…Greater A:P at 10 h indicates oat hulls were being fermented at this time point. It has been well characterised that fermentation of high‐fibre feedstuffs drives production of acetate, whereas fermentation of high‐starch feedstuffs results in greater propionate and butyrate production 23‐25 . While limited data are available on fermentation of oat β‐glucans by equine caecal microorganisms, in vitro fermentation of oat β‐glucans with human faecal inoculum demonstrated increased production of propionate 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Still, concentrates based on cereals such as barley are indispensable due to the high energy demand of athletic horses. However, diets with high concentrate proportion fed to horses facilitate acidification of the hindgut digesta (Hudson, Cohen, Gibbs, & Thompson, ; Sadet‐Bourgeteau, Philippeau, & Julliand, ) and perturbation of the caecal ecosystem (Hudson et al., ). Concentrate feeding was therefore reported to cause changes in the hindgut microbial ecosystem in horses (Grimm, Philippeau, & Julliand, ; Julliand, De Fombelle, Drogoul, & Jacotot, ; Moore & Dehority, ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the cellulolytic bacteria (Julliand et al., ) and the total population of functional bacteria in the colonic contents of horses (Philippeau, Sadet‐Bourgeteau, Varloud, & Julliand, ) are compromised by concentrates like barley. In the literature, it has been shown that feeding concentrate after or along with the forage portion of the diet could, to some extent, help maintaining an appropriate hindgut physiochemical environment (Jensen, Austbø, & Tauson, ; Sadet‐Bourgeteau et al., ; Zeyner, Geiβler, & Dittrich, ). Another attempt to alleviate potential adverse effects of concentrate on hindgut fermentation could consist of the hydrothermal treatment of cereals to make their starch better accessible to digestion in the small intestine and thus reduce the amount of starch arriving in the hindgut and its adverse influence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation